2023
DOI: 10.1007/s12264-023-01072-3
|View full text |Cite
|
Sign up to set email alerts
|

Targeting NAD Metabolism for the Therapy of Age-Related Neurodegenerative Diseases

Abstract: As the aging population continues to grow rapidly, age-related diseases are becoming an increasing burden on the healthcare system and a major concern for the well-being of elderly individuals. While aging is an inevitable process for all humans, it can be slowed down and age-related diseases can be treated or alleviated. Nicotinamide adenine dinucleotide (NAD) is a critical coenzyme or cofactor that plays a central role in metabolism and is involved in various cellular processes including the maintenance of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 210 publications
0
1
0
Order By: Relevance
“…NR has been found to ameliorate tissue nicotinamide adenine dinucleotide (NAD + ) depletion induced by acute kidney injury via increases in autophagy and SIRT1. The induction of NAD + has protective effects against numerous conditions, including diabetes, obesity [19], neurodegenerative diseases, and noise-induced hearing loss [20][21][22]. Lapato et al reported that NR supplementation enhances muscle mitochondrial biogenesis [23].…”
Section: Introductionmentioning
confidence: 99%
“…NR has been found to ameliorate tissue nicotinamide adenine dinucleotide (NAD + ) depletion induced by acute kidney injury via increases in autophagy and SIRT1. The induction of NAD + has protective effects against numerous conditions, including diabetes, obesity [19], neurodegenerative diseases, and noise-induced hearing loss [20][21][22]. Lapato et al reported that NR supplementation enhances muscle mitochondrial biogenesis [23].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing NAD + levels have offered advantages in mitigating the effects of aging and age-related diseases. Many studies have evaluated its impact on neurodegenerative diseases, cardiovascular diseases, metabolic diseases, and cancer [11][12][13][14]. In recent years, NAD + biology has garnered significant attention, prompting the publication of numerous informative review articles exploring its role in various aspects of age-related diseases and longevity [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%